2003
DOI: 10.1002/chem.200305000
|View full text |Cite
|
Sign up to set email alerts
|

Computational Assessment of the Electronic Structure of 1‐Azacyclohexa‐2,3,5‐triene (3δ2‐1H‐Pyridine) and Its Benzo Derivative (3δ2‐1H‐Quinoline) as well as Generation and Interception of 1‐Methyl‐3δ2‐1H‐quinoline

Abstract: Treatment of a solution of 3-bromo-1-methyl-1,2-dihydroquinoline (9) and [18]crown-6 in furan or styrene with KOtBu followed by hydrolysis afforded a mixture of 1-methyl-1,2-dihydroquinoline (10) and 1-methyl-2-quinolone (11). If the reaction was performed in [D(8)]THF and the mixture was immediately analysed by NMR spectroscopy, 2-tert-butoxy-1-methyl-1,2-dihydroquinoline (17) was shown to be the precursor of 10 and 11. The structure of 17 is evidence for the title cycloallene 7, which arises from 9 by beta e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
1
13
0
1
Order By: Relevance
“…Until our communication appeared, Christl and Engels seemed to agree with our usage of nomenclature, since the title of one of their papers10 refers to compound 3 as “1‐azacyclohexa‐2,3,5‐triene”, implying allene 3 a , despite the fact that the ground state of this transient compound was already known to be that of 3‐dehydropyridinium ylide 3 b 11 In other work by Engels et al.,11c a scheme, which is entitled “Possible Electronic Structures of Cyclic Allenes”, shows allene, zwitterion, and diradical forms of a compound.…”
mentioning
confidence: 67%
“…Until our communication appeared, Christl and Engels seemed to agree with our usage of nomenclature, since the title of one of their papers10 refers to compound 3 as “1‐azacyclohexa‐2,3,5‐triene”, implying allene 3 a , despite the fact that the ground state of this transient compound was already known to be that of 3‐dehydropyridinium ylide 3 b 11 In other work by Engels et al.,11c a scheme, which is entitled “Possible Electronic Structures of Cyclic Allenes”, shows allene, zwitterion, and diradical forms of a compound.…”
mentioning
confidence: 67%
“…Until our communication appeared, Christl and Engels seemed to agree with our usage of nomenclature, since the Correspondence title of one of their papers [10] refers to compound 3 as "1-azacyclohexa-2,3,5triene", implying allene 3 a, despite the fact that the ground state of this transient compound was already known to be that of 3-dehydropyridinium ylide 3 b. [11] In other work by Engels et al, [11c] a scheme, which is entitled "Possible Electronic Structures of Cyclic Allenes", shows allene, zwitterion, and diradical forms of a compound.…”
mentioning
confidence: 71%
“…The calculation of the structures 4 b and 5 b indicated this very effect by conspicuously small bond angles of the carbanionic centers. [6,7,9] If 1 c were the correct structure instead of 1 b, the consequence would be a much larger angle, probably as large as that of 2 a, which has been calculated to be 1148. [4] The contribution of the resonance structure 1 d of 1 b to the ground state of the species can only be determined by valence-bond calculations.…”
mentioning
confidence: 99%
“…[8] As more extensive studies confirmed, the allene structure 5 a does not represent an energy minimum. [7,9] If the results of the calculations of 4 and 5 are extrapolated, the coplanar arrangement of the three carbon atoms of the alleged allene system of formula 1 a and its two nitrogen and oxygen atoms has to be expected. According to the X-ray structure analysis performed by Lavallo, Dyker, Donnadieu, and Bertrand, this is perfectly true.…”
mentioning
confidence: 99%